2011
DOI: 10.1007/s00704-011-0575-9
|View full text |Cite
|
Sign up to set email alerts
|

Annual precipitation forecast for west, southwest, and south provinces of Iran using artificial neural networks

Abstract: Rainfed agriculture plays an important role in the agricultural production of the southern and western provinces of Iran. In rainfed agriculture, the adequacy of annual precipitation is considered as an important factor for dryland field and supplemental irrigation management. Different methods can be used for predicting the annual precipitation based on climatic and non-climatic inputs. Among which artificial neural networks (ANN) is one of these methods. The purpose of this research was to predict the annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…These results are in agreement with those of Fallah-Ghalhary et al (2010), who used synoptic patterns including the sea-level pressure, temperature difference, sea-level temperature, relative humidity and sea-level pressure difference for predicting spring rainfall. These results are further compatible with those of El-Shafie et al (2011), Farokhnia et al (2011, Azadi and Sepaskhah (2012), Sanikhani and Kisi (2012)…”
Section: Summary and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with those of Fallah-Ghalhary et al (2010), who used synoptic patterns including the sea-level pressure, temperature difference, sea-level temperature, relative humidity and sea-level pressure difference for predicting spring rainfall. These results are further compatible with those of El-Shafie et al (2011), Farokhnia et al (2011, Azadi and Sepaskhah (2012), Sanikhani and Kisi (2012)…”
Section: Summary and Discussionsupporting
confidence: 93%
“…(), Farokhnia et al . (), Azadi and Sepaskhah (), Sanikhani and Kisi () and Choubin et al . () who reported the superiority of the ANFIS for rainfall prediction.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…So, MLR is not capable enough to predict the wet years and droughts. Azadi and Sepaskhah (2012) suggested that the neural networks did not significantly increase the prediction accuracy compared with the MLR. Dastorani et al (2010) concluded that potential of ANN in dry land precipitation prediction is almost same with the ANFIS model.…”
Section: Discussionmentioning
confidence: 95%
“…Dahamsheh and Aksoy (2009) suggested that the ANNs were slightly better than the multiple linear regression (MLR) in forecasting the monthly total precipitation of arid regions. Azadi and Sepaskhah (2012) concluded that the neural networks did not significantly increase the prediction accuracy compared with the multiple regression model. Dastorani et al (2010) indicated that the potential of ANN in dryland precipitation prediction is almost same with the ANFIS model.…”
Section: Introductionmentioning
confidence: 95%
“…Today, more non-linear models are applied to prediction. In previous studies, Dahamsheh and Aksoy (2009), Azadi andSepaskhah (2012), andRezaeian-Zadeh et al (2012) used artificial neural networks (ANNs), and El-Shafie et al (2011), Sanikhani and Kisi (2012), Jeong et al (2012), and Choubin et al (2014a) successfully applied the adaptive neuro-fuzzy inference system (ANFIS) to predict precipitation. In eastern Australia, Deo and Sahin (2015) investigated the application of the ANN model for the prediction of monthly SPIs using hydrometeorological parameters and climate indices.…”
Section: Introductionmentioning
confidence: 99%